The crisis of race in higher education : a day of discovery and dialogue - Tate, William F.; Staudt, Nancy; Macrander, Ashley (Diversity in higher education ;, 2016)
The compendium of writings in this edited volume sheds light on the event "Race & Ethnicity: A Day of Discovery and Dialogue" at Washington University in St. Louis and the work current students, faculty, and staff are doing to improve inclusivity on campus and in St. Louis. The book includes speeches, reflections, art, and photography aligned with the Day of Discovery and Dialogue in addition to original academic work on race in higher education, race in St. Louis, and race in the United States. Leading scholars and emerging voices feature in this volume, filling a void in the race and higher education literature since it will foreground a case study of a single university at the epicenter of a national racial crisis and how a university-wide event brought a campus together. This praxis focus may have far reaching impact in aiding other universities across the country in addressing racial tensions in their own communities.